2020
DOI: 10.1016/j.gloepi.2020.100036
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of full and partial stay-at-home orders, face mask usage, and contact tracing: An agent-based simulation study of COVID-19 for an urban region

Abstract: Purpose Social intervention strategies to mitigate COVID-19 are examined using an agent-based simulation model. Outbreak in a large urban region, Miami-Dade County, Florida, USA is used as a case study. Results are intended to serve as a planning guide for decision makers. Methods The simulation model mimics daily social mixing behavior of the susceptible and infected generating the spread. Data representing demographics of the region, virus epidemiology, and social int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 32 publications
0
77
0
2
Order By: Relevance
“…However, the advantage of outdoor settings allows the dilution of respiratory droplets much quicker than in indoor environments, which in turn decreases the risk of spread by almost 80% [ 14 ]. Regardless, repeated studies have shown the effectiveness of facemasks in reducing the spread of infection [ 8 , 15 , 16 ], and riding facilities should consider requiring all students and staff to wear facemasks at least when not mounted on a horse. However, knowledge on the spread of COVID-19 is still evolving, and physical distancing rules could be considered based on the factors of the activity undertaken and the ventilation level [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the advantage of outdoor settings allows the dilution of respiratory droplets much quicker than in indoor environments, which in turn decreases the risk of spread by almost 80% [ 14 ]. Regardless, repeated studies have shown the effectiveness of facemasks in reducing the spread of infection [ 8 , 15 , 16 ], and riding facilities should consider requiring all students and staff to wear facemasks at least when not mounted on a horse. However, knowledge on the spread of COVID-19 is still evolving, and physical distancing rules could be considered based on the factors of the activity undertaken and the ventilation level [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in the model presented in [19], each day our model tracks the following for each person: 1) hourly movements for building such a model for another region can be found in [19]. The methodology begins by generating the individual people according to the U.S. census data that gives population attributes including age (see Table A1 in [19]) and occupational distribution (see Table A4 in [19]). Thereafter, it generates the households based on their composition characterized by the number of adults and children (see Table A2 in [19]).…”
Section: Methodsmentioning
confidence: 99%
“…The methodology begins by generating the individual people according to the U.S. census data that gives population attributes including age (see Table A1 in [19]) and occupational distribution (see Table A4 in [19]). Thereafter, it generates the households based on their composition characterized by the number of adults and children (see Table A2 in [19]). The model also generates, per census data, schools (see Table A3 in [19]) and the workplaces and other community locations (see Table A4 in [19]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations